Phytoperspective of Moringa oleifera for oral health care: An innovative ethnomedicinal approach. (22nd October 2020) - Mohanty, Monalisa; Mohanty, Samita; Bhuyan, Sanat Kumar; Bhuyan, Ruchi
Abstract : The present era accentuate the use of alternative medicines as drugs extracted from several plant parts. These herbal medicines otherwise called ethnomedicines are now the source of many imperative drugs in this contemporary world. Furthermore with ever rising oral problems by luxurious lifestyle in this modern society, there is a soaring need for use of potent medicinal plants like horse radish ( Moringa oleifera Lam.) against various oral ailments. Therefore, use of herbal medicines in reducing the adverse effects of various conventional allopathic medicines and harmful side effects of conventional antibiotics has emerged as an evolved technique in pharmaceutical science. The present review emphasizes the antipathogenic potentiality of M. oleifera along with their known therapeutic properties through biologically active compounds (phytoconstituents) and ethnomedicinal uses. Various ethno‐pharmacological studies of the plant parts with their nutritional value and multifarious medicinal uses including oral health care are being quoted in present review. This review will foster future research on phytoconstituent analysis, bioefficacy assessment for oral micro flora and ethno‐pharmaceutical importance of M. oleifera in the field of medical science with special reference to dentistry. Consequently, this innovative ethnomedicinal approach for oral health care may supplement the modern medicine through its potent phytoconstituents.